(3bUjOI aj eOM GdUGMH CHj GdbGSe ESeGYjd Hf YHGO GdWGdbGfjs - (3GdCUagGfj, YHO Gddg Hf eMeO GdNGRfs
(3ChdgG (B:s
(3bGd GdCOjH eMeO YHO Gddg Hf eMeO GdNGRf GdCUagGfj jeOM GdUGMH CHG GdbGSe ESeGYjd Hf YHGO GdWGdbGfj(B: (3gPG aDGOc fgHj Hjf CghG (B*** (3hPGc QCjc ThQG Hjf BQGAs
(3BNQgG (B:s
(3hef efGFM ehdGfG eOGFMg (B*** (3dCf ef RfOg bO Mj hEjQGFjs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdCOHs